Meningkatkan Partisipasi Masyarakat Dalam Pengawasan Pemilu 2024 di Desa Pringgajurang Kecamatan Montong Gading Kabupaten Lombok Timur - Ratna Yuniarti; Sandy Ari Wijaya; Moh. Juhad (Universitas 45 Surabaya, 2023)
Supervision of the implementation of democratic elections requires the role of community participation. However, there are still people who are allergic to politics and show an indifferent attitude towards election activities. This is of course a problem that must be resolved. This PKM activity aims to increase community participation in supervising the 2024 elections. The activity that has taken place in Pringgajurang village has run smoothly. The target participants for this activity are first-time voters. To achieve the target of this activity, the team collaborated with Youth Organization Naga Sunting. The results of this PKM activity showed good results. This activity was quite effective as a first step in imparting basic knowledge of the electoral stages to young people.